2013
DOI: 10.1111/j.1468-0300.2013.12008.x
|View full text |Cite
|
Sign up to set email alerts
|

Bank and Non‐Bank Financial Deepening and Economic Growth: The Nigerian Experience (1981–2010)

Abstract: The paper aimed at empirically investigating the impact of financial deepening on the growth of an economy, with particular emphasis on Nigeria over the period 1981–2010. Financial deepening was segregated to capture both bank and non‐bank financial variables, because both are imperative to economic activities. The study therefore combined a proxy of banking sector development with stock market development to capture the influence of financial deepening on growth. The analysis is based on the bound testing app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
6
0
1
Order By: Relevance
“…Finansal gelişme veya finansal derinleşme olarak tanımlanan bu durumun ekonomik büyümeyi pozitif yönde desteklediğine dair birçok akademik çalışma bulunmaktadır (Patrick, 1966;King ve Levine, 1993;Levine, 1997;Ghali, 1999;Levine, Loayza ve Beck, 2000;Calderon ve Liu, 2003;Apergis vd., 2007;Iyoboyi, 2013;Hamdi vd., 2014;Ghildiyal vd., 2015;Bakang, 2015;Wang, 2019;Sugiyanto ve Yolanda, 2020).…”
Section: Sukuk Ve Ekonomik Büyümeunclassified
“…Finansal gelişme veya finansal derinleşme olarak tanımlanan bu durumun ekonomik büyümeyi pozitif yönde desteklediğine dair birçok akademik çalışma bulunmaktadır (Patrick, 1966;King ve Levine, 1993;Levine, 1997;Ghali, 1999;Levine, Loayza ve Beck, 2000;Calderon ve Liu, 2003;Apergis vd., 2007;Iyoboyi, 2013;Hamdi vd., 2014;Ghildiyal vd., 2015;Bakang, 2015;Wang, 2019;Sugiyanto ve Yolanda, 2020).…”
Section: Sukuk Ve Ekonomik Büyümeunclassified
“…al. (2011), Banerjee (2012), Iyoboyi (2013), Ebi and Emmanuel (2014), Sehrawat and Giri (2015), Mohanty et al (2016) concluded that increase in bank credit (or financial development) leads to higher economic growth. All these studies found significant evidence and consequently supported the supply leading hypothesis.…”
Section: Literaturementioning
confidence: 99%
“…It helps mitigate external financial shocks and ensures the state’s financial security (Timofei, 2015). Growth in the banking sector is a proven predictor of a country's economic growth (Iyoboyi, 2013; Levine and dan Zervos, 1998). The financial performance of companies, including banks, is critical for determining their market value and stakeholders' trust (Santos and Brito, 2012; Lee, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Countries with well-developed banking systems and sound financial institutions experience faster economic growth. Growth in a country’s banking sector has been proven to predict economic growth in that country (Iyoboyi, 2013; Levine and dan Zervos, 1998). Therefore, this study adopts the banking ecosystem as the context to examine leadership roles and values and their interrelation with corporate financial performance.…”
Section: Introductionmentioning
confidence: 99%